Foreign experience of using integrated marketing communications in managing of republic brand (Journal of Economic Research & Business Administration, 2017)
In this work we were considered features of application of integratedmarketing communications in the management of country brand. The authorsanalyzed the international experience of creating a national brand,the problem of creating an attractive brand and evaluation of countrybranding. It was drawn up by positioning the image of the world rankingof countries and made an analysis of the level of use of these countriesintegrated communications. Branding the country will contribute to theeconomic, social, cultural development of the country, most importantlycontributes to the inflow of investment, which in many countries today isa source of livelihood, tourists, increase marketability of domestic products.The authors found that this requires the use of integrated marketingcommunications, the most advanced technology, to engage in the servicesector of local entrepreneurs, thus providing a high level of employmentand income.